Road Expansion and the Fate of Africa's Tropical Forests - Laurance, William F.; Campbell, Mason J.; Alamgir, Mohammed; Mahmoud, Mahmoud I. (Frontiers in Ecology and Evolution, 2017)
The tropical forests of Africa are experiencing unprecedented changes as a result of a rapid proliferation of roads and other infrastructure. These projects are dramatically increasing access to relatively unexploited regions, particularly in the greater Congo Basin. We highlight some of the most important new projects and describe in detail an ongoing debate about a particular proposed development, the Cross River Superhighway in Nigeria. The scale and pace of new transportation projects, and the profound environmental changes they could bring, underscore a dire need for proactive land-use planning, capacity building, and environmental assessment in the nations of Equatorial Africa. It is no exaggeration to suggest that, unless carefully managed to ensure sustainability, the spate of planned and ongoing projects could irreparably diminish the forests and wildlife populations of Africa’s most biologically diverse regions.